Fitness Costs of Maternal Ornaments and Prenatal Corticosterone Manifest as Reduced Offspring Survival and Sexual Ornament Expression - Assis, Braulio A.; Avery, Julian D.; Earley, Ryan L.; Langkilde, Tracy (Frontiers in Endocrinology, 2022)
Colorful traits (i.e., ornaments) that signal quality have well-established relationships with individual condition and physiology. Furthermore, ornaments expressed in females may have indirect fitness effects in offspring via the prenatal physiology associated with, and social consequences of, these signaling traits. Here we examine the influence of prenatal maternal physiology and phenotype on condition-dependent signals of their offspring in adulthood. Specifically, we explore how prenatal maternal testosterone, corticosterone, and ornament color and size correlate with female and male offspring ornament quality and survival to adulthood in the lizard Sceloporus undulatus. Offspring of females with more saturated color and high prenatal corticosterone were less likely to survive to maturity. Badge saturation and area were negatively correlated between mothers and their male offspring, and uncorrelated to those in female offspring. Maternal prenatal corticosterone was correlated negatively with badge saturation of male offspring in adulthood. Our results indicate that maternal ornamentation and prenatal concentrations of a stress-relevant hormone can lead to compounding fitness costs by reducing offspring survival to maturity and impairing expression of a signal of quality in surviving males. This mechanism may occur in concert with social costs of ornamentation in mothers. Intergenerational effects of female ornamentation and prenatal stress may be interdependent drivers of balancing selection and intralocus sexual conflict over signaling traits.